THE APPEARANCE OF «NAFS» IN SUFI LITERATURE AND THE GENESIS OF THIS THEME IN CLASSICAL LITERATURE - Juraeva Muhabbat Amonovna (Web of Journals Publishing, 2024)
This article discusses the appearance of the self in Sufi literature and its educational significance. The article also shows the ways to overcome the self, its progressive art, and its educational significance. In Sufism, people who strive to control their self and take steps towards the beauty of Allah are ranked, and this rank is determined by how much they have overcome their self. For example, a worshiper is a worshiper. It is said that by overcoming the desires and passions associated with the «nafs» and leaving the world, one loves the hereafter. «nafs» is a personality, soul, essence. The inclinations and desires that lead a person astray from the right and noble paths and lead to sins and evils are attributed to the self. A person who has captured the «nafs» is considered a sage.
Keywords: self, Allah, contentment, truth, love, faith, pure, spirit, self, essence, noble, repentance.